Ответ:
Пошаговое объяснение:
![log_{\frac{1}{10} } (x^{2} +3x)= -1\\\\x^{2} +3x=(\frac{1}{10}) ^{-1} log_{\frac{1}{10} } (x^{2} +3x)= -1\\\\x^{2} +3x=(\frac{1}{10}) ^{-1}](https://tex.z-dn.net/?f=log_%7B%5Cfrac%7B1%7D%7B10%7D%20%7D%20%28x%5E%7B2%7D%20%2B3x%29%3D%20-1%5C%5C%5C%5Cx%5E%7B2%7D%20%2B3x%3D%28%5Cfrac%7B1%7D%7B10%7D%29%20%5E%7B-1%7D)
x²+3x=10
x²+3x-10=0
x₁+x₂= -3
x₁x₂= -10
x₁= -5
x₂=2
2
f(x)=x³+5x-8;. x₀=-3
y'(x)=3x²+5
k=y'(x₀)=3*(-3)²+5=32
y₀=y(x₀)= -50
y=32(x+3)-50
y=32x+96-50
y=32x+46
3
V=1/3Sосн.h
Sосн=r²π=14²π=196π см²
V=1/3*196π*20=1306 2/3 π см³
![V=1306\frac{2}{3\ } \pi V=1306\frac{2}{3\ } \pi](https://tex.z-dn.net/?f=V%3D1306%5Cfrac%7B2%7D%7B3%5C%20%7D%20%5Cpi)
4
8\\\\(2^{2} )^{0,5x^{2}-3 } >2^{3} \\\\\\" alt="4^{0,5x^{2}-3 } >8\\\\(2^{2} )^{0,5x^{2}-3 } >2^{3} \\\\\\" align="absmiddle" class="latex-formula">
2(0,5x²-3) > 3
x²-6 > 3
x² > 3+6
x² > 9
x>3
x< -3
x є (-∞;-3) υ (3;+∞)